Non-inferiority of pulsed xenon UV light versus bleach for reducing environmental Clostridium difficile contamination on high-touch surfaces in Clostridium difficile infection isolation rooms. Issue 2 (February 2015) - Ghantoji, Shashank S.; Stibich, Mark; Stachowiak, Julie; Cantu, Sherry; Adachi, Javier A.; Raad, Issam I.; Chemaly, Roy F.
Abstract : The standard for Clostridium difficile surface decontamination is bleach solution at a concentration of 10 % of sodium hypochlorite. Pulsed xenon UV light (PX-UV) is a means of quickly producing germicidal UV that has been shown to be effective in reducing environmental contamination by C. difficile spores. The purpose of this study was to investigate whether PX-UV was equivalent to bleach for decontamination of surfaces in C. difficile infection isolation rooms. High-touch surfaces in rooms previously occupied by C. difficile infected patients were sampled after discharge but before and after cleaning using either bleach or non-bleach cleaning followed by 15 min of PX-UV treatment. A total of 298 samples were collected by using a moistened wipe specifically designed for the removal of spores. Prior to disinfection, the mean contamination level was 2.39 c.f.u. for bleach rooms and 22.97 for UV rooms. After disinfection, the mean level of contamination for bleach was 0.71 c.f.u. ( P =0.1380), and 1.19 c.f.u. ( P =0.0017) for PX-UV disinfected rooms. The difference in final contamination levels between the two cleaning protocols was not significantly different ( P =0.9838). PX-UV disinfection appears to be at least equivalent to bleach in the ability to decrease environmental contamination with C. difficile spores. Larger studies are needed to validate this conclusion. Abbreviations: CDI, C. difficile infection; PX, pulsed xenon.